Pentingnya Manajemen Organisasi Pendidikan - Uswatun Hasanah; Siti Nurhaliza; Salsabila Hayatissa'idah; Indah Nurhaliza; Luthfia Zahra (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to understand the function, purpose, and urgency of the importance of management in organizational education. This research uses qualitative research. This research method uses the library research method of collecting data by searching for sources and reconstructing from various sources such as books, journals, and existing research and taking opinions, explanations from previous studies. In achieving goals, an organization needs to have good management. Vice versa, to have the best management, the organization must have people who are skilled, creative, and able to work in teams to realize organizational goals. Therefore, good cooperation between the organization and management is necessary. By utilizing resources and time appropriately according to the established activity process, goals can be achieved more efficiently, effectively, and optimally. If both are carried out in accordance with their duties, the reciprocal relationship will be mutually beneficial for both. The importance of education management today should be a priority to ensure the continuity of education that produces the desired graduates. Currently, many educational institutions do not have effective management in managing their education. The management used is still conventional, so it is not fully able to overcome the challenges of the times and looks behind in terms of modernity. So, in the process of its development, Education Management requires what is called Good Management Practice to manage it.